2010
DOI: 10.4103/0974-777x.68525
|View full text |Cite
|
Sign up to set email alerts
|

Surveying infections among pregnant women in the Niger Delta, Nigeria

Abstract: Background:There is paucity of epidemiological data on infectious diseases among antenatal mothers in Bayelsa State of the Niger Delta, Nigeria.Aims:The aim of this study was to determine the seroprevalence of the serological markers Human immunodeficiency virus-antibody (HIV-Ab), Hepatitis B surface antigen(HBsAg), Hepatitis C virus antibody(HCV-A)and antibodies to T. pallidum among pregnant women in Yenagoa, Bayelsa State, South–South Nigeria.Settings and Design:This is a cross-sectional study which was carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 26 publications
3
18
4
Order By: Relevance
“…This study showed that pregnant women who are unmarried, women in a polygamous marriage, women living in a separate house from husbands and women married to frequently traveling husbands were more likely to seroconvert. Other similar studies have also shown that single mothers,[ 7 ] polygamous relationship and multiple sexual partners. [ 6 12 17 ] are potential risk factors for HIV seroconversion among pregnant women.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…This study showed that pregnant women who are unmarried, women in a polygamous marriage, women living in a separate house from husbands and women married to frequently traveling husbands were more likely to seroconvert. Other similar studies have also shown that single mothers,[ 7 ] polygamous relationship and multiple sexual partners. [ 6 12 17 ] are potential risk factors for HIV seroconversion among pregnant women.…”
Section: Discussionmentioning
confidence: 86%
“…[ 6 12 ] Pregnant women at the peak of reproductive age (25–30 years) in the present study were more likely to seroconvert (7.2%), although the difference was not statistically significant ( P = 0.09), other similar study showed the difference to be statistical significant (15–34 years, P < 0.005). [ 7 ] Suggesting that this age range may be associated with higher sexual activities. Similar to other studies,[ 6 15 ] high seroconversion rate was shown among pregnant women married to mobile husbands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in agreement with the overall seroprevalence of HCV in sub-Saharan Africa 3%. [ 7 ] It is however, higher than the result from Niger Delta, Nigeria 0.5%,[ 20 ] Iran 0.98%,[ 25 ] and Sudan <1%. [ 22 ] These variations may be related to the differences in the modes of transmission, which is influenced by socio-cultural practices and environmental factors.…”
Section: Discussionmentioning
confidence: 96%
“…[ 22 ] These variations may be related to the differences in the modes of transmission, which is influenced by socio-cultural practices and environmental factors. [ 20 ] In a tertiary medical center in South-West Nigeria where over 90.8% of the women had scarification marks, a seroprevalence of 9.2% was reported. [ 9 ] The differences have also been attributed to the choice of serological tests to determine HCV prevalence especially in developing countries where intercurrent infections contribute to false-positive enzyme immunoassay results.…”
Section: Discussionmentioning
confidence: 99%